A Comparative Cross-sectional Study on Amblyopia and its Relationship with Retinal Nerve Fiber Layer Thickness. - Saeed, Muhammad Asad; Sadaat, Azka; Ayub, Fareeha; Aziz, Amtul; Fatima, Rida; ul Ain, Qurat (Optometry & Visual Performance, 2026)
Background: Amblyopia affects approximately 1.75% of the world's population. Atrophic alterations in the lateral geniculate nucleus have been observed in amblyopic eyes, leading to the hypothesis that retinal nerve fiber layer (RNFL) thickening is caused by a limitation of normal postnatal ganglionic cell reduction. This study was conducted to determine and compare the thickness of the RNFL in all types of amblyopic and non-amblyopic eyes. Methods: A comparative cross-sectional study was conducted at Al-Shifa Trust Eye Hospital Rawalpindi over six months. Data were collected from 70 patients (140 eyes) using a clinical structured questionnaire. RNFL thickness was measured using optical coherence tomography. All amblyopic patients were included in this study. A one-way ANOVA and paired sample t-test were applied to compare the RNFL thickness between amblyopic and non-amblyopic eyes. Results: The mean age of the patients was 10.20±2.811, ranging from 5 to 16 years. The mean thickness of RNFL globally in strabismic amblyopia was 108.1±14.1, whereas in anisometropic and bilateral refractive amblyopia, the RNFL thickness was 105.74±11.042 and 107.84±12.329, respectively. There was no statistical mean difference between thicknesses of strabismus, anisometropic, and bilateral amblyopia. There was no statistically significant difference found between the thicknesses among all quadrants of anisometropic amblyopia. Conclusion: There was no significant difference in RNFL thickness between different types of amblyopia. Similarly, there was no significant difference in the thickness of RNFL in amblyopic and non-amblyopic eyes.